Broadening the Analysis of Canadian Healthcare Reforms - Mark Exworthy and Russell Mannion (HealthcarePapers, 2025)
Analysis of any healthcare reform is complex and multi-faceted. Given the hierarchical levels in health systems (regarding funding and accountability, etc.), a key analytical dimension is between decentralization and centralization. Reforms can be justified on either, often for the same criteria (such as equity or economy). The impact of decentralization/centralization can be assessed by determining “what” is being (de)centralized and from/to whom. This article appraises the analysis of Canadian healthcare reform by Denis, in terms of the TAPIC (Transparency, Accountability, Participation, Integrity and Capability) and decision space frameworks. It draws attention to the importance of incentives, context and implementation in this (and other) reform program.
Keywords: decentralization; centralization; governance; decision space; autonomy